Board Expertise: Do Directors from Related Industries Help Bridge the Information Gap? - Dass, Nishant; Kini, Omesh; Nanda, Vikram; Onal, Bunyamin; Wang, Jun (Review of Financial Studies, 2014)
We analyze the role of "directors from related industries" (DRIs) on a firm's board. DRIs are officers and/or directors of companies in the upstream/downstream industries of the firm. DRIs are more likely when the information gap vis-à-vis related industries is more severe or the firm has greater market power. DRIs have a significant impact on firm value/performance, especially when information problems are worse. Furthermore, DRIs help firms handle industry shocks and shorten their cash conversion cycles. Overall, our evidence suggests that firms choose DRIs when the adverse effects due to conflicts of interest are dominated by the benefits due to DRIs' information and expertise.